Historical Landscape Use of Migratory Caribou: New Insights From Old Antlers - Miller, Joshua H.; Crowley, Brooke E.; Bataille, Clément P.; Wald, Eric J.; Kelly, Abigail; Gaetano, Madison; Bahn, Volker; Druckenmiller, Patrick (Frontiers in Ecology and Evolution, 2021)
Accumulations of shed caribou antlers are valuable resources for expanding the temporal scope with which we evaluate seasonal landscape use of herds. Female caribou shed their antlers within days of giving birth, thus marking calving ground locations. Antler geochemistry (87Sr/86Sr) reflects the isotopic signature of regions used during antler growth, thereby providing data on a second component of seasonal landscape use. Here, we evaluate shed caribou antlers from the Coastal Plain of the Arctic National Wildlife Refuge, Alaska. The Central and Eastern regions of the Coastal Plain are calving grounds for the Porcupine Caribou Herd, while the Western Coastal Plain supports calving by the Central Arctic Herd. We found that antler 87Sr/86Sr from the Central and Eastern Coastal Plain were isotopically indistinguishable, while antler 87Sr/86Sr from the Western Coastal Plain was significantly smaller. For each region, we compared isotopic data for “recent” antlers, which overlap the bulk of standardized state and federal caribou monitoring (early 1980s and younger), with “historical” antlers shed in years predating these records (from the 1300s to the 1970s). For Porcupine Herd females calving in the Arctic Refuge, comparisons of antler 87Sr/86Sr through time indicate that summer ranges have been consistent since at least the 1960s. However, changes between historical and recent antler 87Sr/86Sr for the Central Arctic Herd indicate a shift in summer landscape use after the late 1970s. The timing of this shift is coincident with multiple factors including increased infrastructural development in their range related to hydrocarbon extraction. Accumulations of shed caribou antlers and their isotope geochemistry extend modern datasets by decades to centuries and provide valuable baseline data for evaluating potential anthropogenic and other influences on caribou migration and landscape use.